(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2026)
The security of home access is a critical aspect of asset protection and occupant safety. Conventional security systems using physical keys have weaknesses such as potential key loss, illegal duplication, and a lack of access records. This research develops Smart Door Guardian, an intelligent door security system that integrates RFID technology, the ESP32-CAM microcontroller, a servo motor lock mechanism, a reed switch sensor, and real-time notifications via the Telegram Bot API. The system operates by reading RFID cards; if registered, the servo motor rotates to unlock the door, and the ESP32-CAM captures and sends the user’s image to the administrator. Conversely, forced entry attempts are detected by the reed switch, triggering an intruder’s alert and photo capture. Test results show an RFID reading accuracy of 98.7%, an average photo notification speed of 2.3 seconds, and a 100% detection accuracy for forced entry at a 5 mm gap. This system provides an effective, low-cost IoT solution for room security.